Relationship between the dehydration temperature of Boehmite and the imperfection structure of γ-alumina - Jian-Min, Hao (Polyhedron, 1996)
The relationship between the imperfection structure of γ-alumina formed by dehydration of Boehmite and the dehydration temperatures is established by analysing the integral width of X-ray reflections. Characterization of the imperfection structure is by calculation of average sizes of the aluminum and oxygen sublattices, and the lattice strains. Two types of stacking faults are introduced to explain the imperfection structure. One type of stacking fault appears at low dehydration temperatures and has more influence on the aluminum sublattice, the other formed at higher dehydration temperatures affects the oxygen sublattice.